Molecular and Clinical Characterization of PD-1 in Breast Cancer Using Large-Scale Transcriptome Data - Liu, Qiang; Cheng, Ran; Kong, Xiangyi; Wang, Zhongzhao; Fang, Yi; Wang, Jing (Frontiers in Immunology, 2020)
Despite the impressive impact of PD-1 (programmed cell death protein 1)-targeted cancer immunotherapy, a great part of patients with cancer fail to respond. PD-1 impact on immune cells in addition to T cells, and the synergistic role of PD-1 with other immune modulators remain largely unknown. To fill this gap, we systematically investigated PD-1-related transcriptome data and relevant clinical information derived from TCGA (The Cancer Genome Atlas) and METABRIC (Molecular Taxonomy of Breast Cancer International Consortium), which involved a total of 2,994 breast cancer patients. Our results revealed the relationship among PD-1 and major molecular and clinical characteristics in breast cancer. More importantly, we depicted the association landscape between PD-1 and other immune cell populations. Gene ontology analyses and gene set variation analysis (GSVA) of genes correlated with PD-1 revealed that PD-1 was mainly involved in immune responses and inflammatory activities. We also elucidated the association of PD-1 with other immune modulators in pan-cancer level, especially the potential synergistic relationship between PD-1 and other immune checkpoints members in breast cancer. In short, the expression level of PD-1 was bound up with breast cancer malignancy, which could be used as a potential biomarker; PD-1 might manipulate the anti-tumor immune response by impacting not just T cells, and this might vary among different tumor types. Furthermore, PD-1 might synergize with other immune checkpoint members to modulate the immune microenvironment in breast cancer.